ELECTRONIC AND COMPUTER GAMES. - Haddon, Leslie (Screen)
The article examines the history and development of interactive computer games. It states that the earliest known computer games were developed in the early 1960s in U.S. computing institutions, using DEC microcomputers. Computer programmers known as hackers, were the first to exploit the use of computers not only as administrative tools but an object of entertainment. According to the author, computer games gave rise to arcade games, which appeared as two different types of commercial products: the coin-operated arcade game, and the home machine. Home video machines served as an extension of the television, differing from the later home computer due to its lack of a keyboard and programming language, the author says.